Comparative study of using the Neodymium-doped yttrium Aluminium Garnet laser alone or in combination with the High Intensity Focussed Ultrasound technique for removing the professional tattoo - Sahar Saadon Baker,; Jamal Abduljabar Hasan,; Mustafa Al Musawi, (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effects of combining neodymium-doped yttrium aluminium garnet laser and high-intensity focussed ultrasound techniques to remove a professionally-done tattoo. Method: The interventional study was conducted from November 2021 to April 2022 at the at the Postgraduate Medical Physics Laboratory of Mustansiriyah University, Baghdad, Iraq, and comprised healthy adults aged 18-60 years who wished to have their tattoo areas from their hands, arms and forearms removed. Each tattoo was divided into 3 areas. The first area was treated with multiple passes of neodymium-doped yttrium aluminium garnet laser with 450mJ. The second area was treated with multiple passes of neodymium-doped yttrium aluminium garnet laser with 450mJ and 850mJ. The third area was treated with multiple passes of neodymium-doped yttrium aluminium garnet laser with 450mJ, followed by 5-10 consecutive strokes of HIFU waves with energy 0.25-0.6mJ, 1.4mm depth, 10MHz and 7MHz frequency, and a second blow of the neodymium-doped yttrium aluminium garnet laser with 450mJ. The intervention lasted 8 sessions, and the time required between the sessions ranged 15-20 days. The percentage of pigmentation was evaluated using the image segmentation method based on fuzzy c-means. Data was analysed using SPSS 24. Results: Of the 20 subjects, 12(60%) were males and 8(40%) were females. There were 10(50%) subjects aged 17-24 years, 6(30%) aged 25-35 years and 4(20%) aged 36-45 years. The tattoo pigments showed a significant reduction in all the 3 groups (p<0.05), but intergroup comparison showed that the reduction was most significant in the group treated with neodymium-doped yttrium aluminium garnet laser plus high-intensity focussed ultrasound (p<0.05). Conclusion: The combination of high-intensity focussed ultrasound and neodymium-doped yttrium aluminium garnet laser led to more positive outcome compared to the use of low- or high-intensity laser alone. Key Words: Tattooing, Lasers, Forearm, Pigmentation,